Effects of various number of basal and covering polyelectrolyte layers on immobilized enzyme activity - Shojaei, Seyedeh Sara (Jihočeská univerzita, 2022)
This thesis is focused on the immobilization of a selected biomolecule, Horseradish peroxidase enzyme (HRP), into a polyelectrolyte multilayer on the glass surface in order to investigate HRP stability and activity in time and specific conditions. To accomplish this work, layer-by-layer deposition approach is employed to fabricate a multilayer of polystyrene sulfonate (PSS) and polyallylamine hydrochloride (PAH). Therefore, 0.1 ěg of HRP enzyme is immobilized onto the various constructs with different number of basal and covering PSS and PAH polyelectrolyte layers. As a results, the activity of the enzyme is increased by further underlying PSS and PAH polyelectrolyte layers. The enzyme activity of the constructs which are not covered by PSS/PAH polyelectrolyte layers is diminished, whereas the enzyme activity of constructs which are covered by the PSS/PAH polyelectrolyte layers is increased.
Effects of various number of basal and covering polyelectrolyte layers on immobilized enzyme activity
Keywords: Layer-by-Layer deposition; Enzyme immobilazation; Horseradish peroxidase; Polyelectrolyte layers; Surface modification; Enzyme acitivity; Layer-by-Layer deposition; Enzyme immobilazation; Horseradish peroxidase; Polyelectrolyte layers; Surface modification; Enzyme acitivity